A genomics approach reveals the global genetic polymorphism, structure, and functional diversity of ten accessions of the marine model diatom Phaeodactylum tricornutum - Rastogi, Achal (ISME J, 2019)
Diatoms emerged in the Mesozoic period and presently constitute one of the main primary producers in the world’s ocean and are of a major economic importance. In the current study, using whole genome sequencing of ten accessions of the model diatom Phaeodactylum tricornutum, sampled at broad geospatial and temporal scales, we draw a comprehensive landscape of the genomic diversity within the species. We describe strong genetic subdivisions of the accessions into four genetic clades (A–D) with constituent populations of each clade possessing a conserved genetic and functional makeup, likely a consequence of the limited dispersal of P. tricornutum in the open ocean. We further suggest dominance of asexual reproduction across all the populations, as implied by high linkage disequilibrium. Finally, we show limited yet compelling signatures of genetic and functional convergence inducing changes in the selection pressure on many genes and metabolic pathways. We propose these findings to have significant implications for understanding the genetic structure of diatom populations in nature and provide a framework to assess the genomic underpinnings of their ecological success and impact on aquatic ecosystems where they play a major role. Our work provides valuable resources for functional genomics and for exploiting the biotechnological potential of this model diatom species.